Influenza A virus infection of intestinal epithelial cells enhances the adhesion ability of Crohn's disease associated Escherichia coli strains. - Marta Aleandri; Maria Pia Conte; Giovanna Simonetti; Simona Panella; Ignacio Celestino; Paola Checconi; Massimiliano Marazzato; Catia Longhi; Paola Goldoni; Mauro Nicoletti; Nicolas Barnich; Anna Teresa Palamara; et al. (PLoS ONE)
Modifications of intestinal glycoreceptors expression, in particular CEACAM6, typically found in ileal Crohn's disease (CD), favor, among the commensal species of microbiota, the enrichment in Escherichia coli. Removal of protein glycosidic residues by neuraminidase, a sialidase typical of influenza virus, increases adhesion ability of Escherichia coli to Caco-2 intestinal cells. In this study we investigated whether influenza virus infection of human intestinal epithelial cells could influence the adhesiveness of different Escherichia coli strains isolated from CD patients by altering surface glycoreceptors. Influenza virus infection of intestinal cells increased exposure of galactose and mannose residues on the cell surface. In particular, glycoreceptors Thomsen-Friedenreich and CEACAM6 were over-expressed in influenza virus infected cells. In the same experimental conditions, a significant increase in bacterial adhesiveness was observed, independently of their own adhesive ability. The increase was reverted by treatment with anti-TF and anti-CEACAM6 antibodies. Interestingly, influenza virus was able to efficiently replicate in human primary intestinal cells leading to TF exposure. Finally, intestinal infected cells produced high levels of pro-inflammatory cytokines compared to control. Overall these data suggest that influenza virus infection, could constitute an additional risk factor in CD patients.